Memantine and Riluzole Exacerbate, Rather Than Ameliorate Behavioral Deficits Induced by 8-OH-DPAT Sensitization in a Spatial Task - Janikova, Martina; Mainerova, Karolina; Vojtechova, Iveta; Petrasek, Tomas; Svoboda, Jan; Stuchlik, Ales (Biomolecules, 2021)
Chronic sensitization to serotonin 1A and 7 receptors agonist 8-OH-DPAT induces compulsive checking and perseverative behavior. As such, it has been used to model obsessive-compulsive disorder (OCD)-like behavior in mice and rats. In this study, we tested spatial learning in the 8-OH-DPAT model of OCD and the effect of co-administration of memantine and riluzole-glutamate-modulating agents that have been shown to be effective in several clinical trials. Rats were tested in the active place avoidance task in the Carousel maze, where they learned to avoid the visually imperceptible shock sector. All rats were subcutaneously injected with 8-OH-DPAT (0.25 mg/kg) or saline (control group) during habituation. During acquisition, they were pretreated with riluzole (1 mg/kg), memantine (1 mg/kg), or saline solution 30 min before each session and injected with 8-OH-DPAT ("OH" groups) or saline ("saline" groups) right before the experiment. We found that repeated application of 8-OH-DPAT during both habituation and acquisition significantly increased locomotion, but it impaired the ability to avoid the shock sector. However, the application of 8-OH-DPAT in habituation had no impact on the learning process if discontinued in acquisition. Similarly, memantine and riluzole did not affect the measured parameters in the "saline" groups, but in the "OH" groups, they significantly increased locomotion. In addition, riluzole increased the number of entrances and decreased the maximum time avoided of the shock sector. We conclude that monotherapy with glutamate-modulating agents does not reduce but exacerbates cognitive symptoms in the animal model of OCD.
Keywords: Obsessive-Compulsive Disorder; Riluzole; Behavior, Animal; memantin; obsessive-compulsive disorder; Rats; prostorové učení; Male; riluzol; potkani Long-Evans; Memory; Disease Models, Animal; mužské pohlaví; spatial learning; Spatial Learning; krysa rodu Rattus; paměť; 8-hydroxy-2-(di-N-propylamino)tetralin; modely nemocí na zvířatech; zvířata; chování zvířat; Rats, Long-Evans; riluzole; memory; memantine; Memantine; 8-OH-DPAT; obsedantně kompulzivní porucha; 8-Hydroxy-2-(di-n-propylamino)tetralin; Animals